ACCOUNTING TRAINING FOR THE GOVERNMENT SERVICE. - Massel, Mark S. (The Accounting Review, 1945)
Accounting training for the government service seems to be headed for a much larger role in the accounting curriculum than it had before the war. Most of the reasons for this trend existed before the war, although wartime problems have reinforced them. The problems of accounting training for the government service are not peculiar to the government service except in the case of fiscal operations. In general, the requirements of government and the parallel requirements of industry present an excellent opportunity for a dynamic accounting program in universities. As a result of the experience afforded by the war, the changes, which may be required, can be made more easily. Accountants have more information in a great many fields than ever before. There is a growing feeling in all walks of life that the professional groups must break out of their insulated pigeonholes. Many people in other fields are aware of this situation and are making plans to correct it. The accounting group has an interesting time ahead of it.